(NaNIZOTROPIQ POGLO]ENIQ I L@MINESCENCII MNOGOATOMNYH MOLEKUL (B/s - (NgAJSENOK(B, (NwIKTOR aNATOLXEWI^s; (NsARVEWSKIJ(B, (NaLEKSANDR mIHAJLOWI^s ((NmINSK (B:s (NuNIWERSITETSKOE(B,s, 1986)
(NbIBLIOGR(B.: (NS(B. 286-316s
Keywords: (NmOLEKULY (B- (NaNIZOTROPIQ OPTI^ESKAQs; (NoRGANI^ESKIE SOEDINENIQ (B- (NaNIZOTROPIQ OPTI^ESKAQs